The effect of witnessing domestic violence among children in Tafelkop, Limpopo Province, South Africa - Nkadimeng, Cashline (My University, 2024)
Background: Domestic violence is a widespread problem that has serious consequences, especially for children who experience it. When children see or go through these upsetting situations, it leaves them with emotional scars that affect different parts of their lives. The purpose of this study was to explore and describe the effect of witnessing domestic violence among children in Tafelkop, Limpopo Province. Methodology: This study used a qualitative approach and an exploratory research design. Purposive sampling was used to select 13 children between the age of 8-18 years from Matsepe Drop-in Centre to participate in this study. The sample size was depended on data saturation. One-on-one interviews were conducted with participants using semi-structured interview guide. Data was analyzed using Tesch‘s 8 steps of open coding method. Trustworthiness was ensured through credibility, transferability, dependability, and confirmability. The study was approved by TREC (University of Limpopo Ethics Committee), and permission to conduct the study was granted. Confidentiality, anonymity and privacy of participants were assured. Informed consent was obtained from participants prior their participation. Results: This study found that children who see domestic violence get scared, and this causes problems like wanting to run away from home, avoiding arguments, and feeling emotions like being really mad or sad. Additionally, the study found that when children witness domestic violence, they might develop issues with anger. This can show up as bullying or being aggressive, feeling frustrated a lot, acting out in a mean way, and having big tantrums. The research also showed that children feeling shame or guilt during domestic violence might face long-term effects. They might isolate themselves, struggle to focus, lose interest in things they liked before, and even skip school to cope with these feelings of shame or guilt. Conclusion: This study highlights the severe impact of domestic violence on children, causing fear and various negative outcomes such as anger issues, bullying, and emotional struggles. The findings indicate the importance of early interventions led by professionals such as social workers and school counsellors. Community-wide awareness campaigns are also recommended to educate the public about the harmful effects of domestic violence on children and the crucial role of intervention and support.
Thesis (MPH.) -- University of Limpopo, 2024
Keywords: Anger; Children; Fear; Isolation; Witnessing domestic violence; Family violence; Fear in children